2020
DOI: 10.24018/ejbmr.2020.5.4.448
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of Innovation Management Against Unique Resources To Enhance The Business Performance of Small And Medium Enterprises (Sme) In Pasar Tanah Abang, Jakarta, Indonesia

Abstract: The objective of this research is to analyze the business performance of the small and medium enterprises (SME) textile industries in Pasar Tanah Abang, Jakarta, Indonesia in order to find out how these SME industries can survive with the competition of thousands of SME in this area. This research is to analyze the implication of innovation management as the intervening variable that influence the unique resources and market orientation used by the SME industries to improve their business performance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Respondents revealed that the number of novice businessmen or newcomers who helped enliven online sales with similar goods, various sellers accompanied by prices that were much cheaper than the market price could turn off other entrepreneurs, so innovation and creativity are needed. According to (Ramli, 2020), innovation can affect business performance and aims to achieve comparative advantage, because if lowering prices to remain competitive is not easy to do, it is related to production costs in the midst of the economic crisis due to the pandemic and the ongoing PSBB policy. This is in accordance with study conducted by (Saturwa, et al, 2021), so that E-Commerce Readiness and online business players are very important during times of uncertainty such as the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents revealed that the number of novice businessmen or newcomers who helped enliven online sales with similar goods, various sellers accompanied by prices that were much cheaper than the market price could turn off other entrepreneurs, so innovation and creativity are needed. According to (Ramli, 2020), innovation can affect business performance and aims to achieve comparative advantage, because if lowering prices to remain competitive is not easy to do, it is related to production costs in the midst of the economic crisis due to the pandemic and the ongoing PSBB policy. This is in accordance with study conducted by (Saturwa, et al, 2021), so that E-Commerce Readiness and online business players are very important during times of uncertainty such as the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This type of tourism is distinguished from other special interests, such as nature tourism, historical tourism, and adventure tourism. The attractiveness of cultural tourism lies in the lifestyle, values, and beliefs that are firmly held by customs or tourists who need other cultural experiences that have never been encountered (Asih et al, 2020;Rohman et al, 2020;Ramli and Soelton, 2018). One reason for the increasing interest in cultural tourism is the longing for cultural values that are still strong, such as religious values, art, language, and lifestyles that are different from those of modern tourists.…”
Section: Introductionmentioning
confidence: 99%
“…This perspective states that a leader is said to be successful if he can utilize unique and different internal resources as the company's strength to compete with others. (Astuti, Sanawiri and Iqbal, 2020;Ramli, 2020;Suroso et al, 2021;Bakaritantri, 2022). Thus, this study aims to explore the ups and downs of MSMEs by analyzing the innovation strategies carried out by MSMEs in the period before and after the Covid 19 pandemic with a case study of the Kepanjen Coffee Omahan business.…”
Section: Introductionmentioning
confidence: 99%